Бактерицидні властивості етанольних екстрактів рослин на мікроорганізми роду Staphylococcus - Зажарський, Володимир Володимирович; Zazharskiy, Volodymyr; Zazharskyi, Volodymyr; Zazharskiy, Vladymyr; Zazharskyi, Vladymyr; Давиденко, Павло Олександрович; Davydenko, Pavel; Кулішенко, Олег Миколайович; Kulishenko, Oleg; Боровик, Ірина Володимирівна; Borovic, Irina (Інститут ветеринарної медицини НААН, 2018)
У роботі наведено результати ефективності фітопрепаратів до Staphylococcus aureus, Staphylococcus epidermidis в системі in vitro. Виявлено антибактеріальний вплив рослинних настоянок Елеутерококу колючого, Елеутерококу сидячеквіткового та Гранату звичайного на еталонний кріогенний штам Staphylococcus aureus F-4a (АТСС №25923); настоянок Гранату звичайного та прополісу бджолиного на штам Staphylococcus epidermidis (14990). Отримані результати дають підставу рекомендувати рослинні настоянки для боротьби з полірезистентними штамами роду Staphylococcus. The emergence of multiresistant strains of staphylococci that are difficult to antibiotics and cause severe lesions of soft tissues, sepsis, and complicated surgical pathology are recognized as the one of problems of current infectious diseases of animals and humans. One of challenges in pharmacognosy is the search for alternative sources of antibacterial substances with an exhaustive resource of antibiotics of fungal origin. The use of raw medicinal plants is quite promising in this regard. The tendency of scientific research of recent decade reveals a promising range of plants of a number of families, which typically contents certain active substances (phytoncides, saponins, alkaloids, glycosides, tannins, essential oils etc.).
Bacterial properties of ethanol extracts of phytopreparation a Staphylococcus spp
Keywords: антибактеріальна активність; antibacterial activity; рослинні настоянки; plant infusions